Impacts of Droughts and Acidic Deposition on Long-Term Surface Water Dissolved Organic Carbon Concentrations in Upland Catchments in Wales - Lee, Jaeyoung; Whitehead, Paul G.; Futter, Martyn N.; Hall, Jim W. (Frontiers in Environmental Science, 2020)
Concerns have been raised about rising trends in surface water dissolved organic carbon (DOC) concentrations in UK upland catchments over the past decades. Several mechanisms have been proposed to explain these trends, including changes in climate and declines in sulfate deposition across Europe. Drier summers and wetter winters are projected in the UK, and there is an increasing interest in whether the rising trends of DOC would be continued or stabilized. In this paper, the INCA (INtegrated CAtchment) water quality model was applied to the upland catchment of the River Severn at Plynlimon in Wales and used to simulate the effects of both climate and sulfate deposition on surface water DOC concentrations. We introduced new parameter sets of INCA to explain enzymatic latch effect in peatlands during droughts. The model was able to simulate recent past (1995–2013) rising trends in DOC in Plynlimon. Climatic projections were employed to estimate the future trends on DOC in the uplands and to consider potential impacts on catchment management. The model was run with climatic scenarios generated using the weather@home2 climate modeling platform and with sulfate deposition scenarios from the European Monitoring and Evaluation Programme (EMEP) for 1975–2100. The modeling results show that the rising DOC trends are likely to continue in the near future (2020–2049) and the level of DOC concentrations is projected to stabilize in the far future (2070–2099). However, in the far future, the seasonal patterns of DOC concentrations will change, with a post-drought DOC surge in autumn months.